2018
DOI: 10.1002/pd.5249
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical application of chromosomal microarray analysis for the prenatal diagnosis of chromosomal abnormalities and copy number variations in fetuses with congenital heart disease

Abstract: This study shows that CMA is particularly effective for identifying chromosomal abnormalities and CNVs in fetuses with CHDs as well as having an effect on obstetrical outcomes. The elucidation of the genetic basis of CHDs will continue to expand our understanding of the etiology of CHDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
3
16
1
Order By: Relevance
“…Among the fetuses with sonographic structural malformations, those with multiple malformations showed the greatest rate of CNVs (31.8%, 7/22), followed by fetuses with central nervous system malformations (25%, 4/16), congenital anomalies of the kidney and urinary tract (18.0%, 7/39), and congenital heart malformations (8%, 10/125). These findings are slightly different from those of a previous study 13 , in which cardiovascular, central nervous, gastrointestinal, and musculoskeletal system malformations were mostly associated with pathogenic CNVs.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the fetuses with sonographic structural malformations, those with multiple malformations showed the greatest rate of CNVs (31.8%, 7/22), followed by fetuses with central nervous system malformations (25%, 4/16), congenital anomalies of the kidney and urinary tract (18.0%, 7/39), and congenital heart malformations (8%, 10/125). These findings are slightly different from those of a previous study 13 , in which cardiovascular, central nervous, gastrointestinal, and musculoskeletal system malformations were mostly associated with pathogenic CNVs.…”
Section: Discussioncontrasting
confidence: 99%
“…25,26 One recent fetal cohort reported a prevalence of 16% pathogenic CNVs. 27 This proportion, however, reflects a selected population, as they only included those referred for invasive genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the prevalence of abnormal CNVs was significantly higher in fetuses with cardiac and extracardiac malformations than in those with single or multiple cardiac malformations (P<0.05), and a high detection of abnormal CNVs was seen in fetuses with multiple cardiac malformations than in those with a single cardiac malformation (P<0.05), which was inconsistent with previous reports. [38][39][40] This may be because more fetuses with CHD were enrolled in our study, and the number of subjects was comparable among groups. Compared with previous studies, [38][39][40] this study is more persuasive, and our data demonstrate a strong correlation between fetal multiple malformations and abnormal CNVs.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] This may be because more fetuses with CHD were enrolled in our study, and the number of subjects was comparable among groups. Compared with previous studies, [38][39][40] this study is more persuasive, and our data demonstrate a strong correlation between fetal multiple malformations and abnormal CNVs.…”
Section: Discussionmentioning
confidence: 99%